P-cadherin expression in oral mucosa of smoker patients : An immunohistochemical study - Sherien Ali Hassan; Hossam Eldin Hussein; Shaheenaz Gamal Eldin Elashery; Soheir Mohamed Gaafar (Cairo : Sherien Ali Hassan, 2009)
The aim of our study is to assess the prevalence of P-CD expression in oral mucosa of smoker patients with and without oral smoker's keratosis and verify whether P-CD could be considered as a marker of prognosis in thses patients. Our results revealed basal and parabasal expression of P-CD in group 1, while, group 11 and 111 expressed P-CD in all epithelial cell layers except the keratin
Thesis (M.Sc.) - Cairo University - Faculty of Oral and dental Medicine - Department of Oral-Radiology and Diagnosis
Issued also as CD
Keywords: P-CD; Smokers; Tobacco